Interprofessional Collaboration in Patients Diabetes Mellitus: A Case Study - Afandi, Alfid Tri; Candrayani, Melis; Ardiana, Anisah; Fariasih, Cucik (Jurnal Kesehatan Komunitas Indonesia, 2023)
Interprofessional collaboration (IPC) is cooperation between health professionals who work together to solve health problems, provide medical services, and achieve common goals. In the health sector, 70-80% of errors are due to poor communication and understanding within the team. In Indonesia, one result of the lack of coordination between medical personnel is the high error rate in prescribing drugs, which is up to 98.69%. Communication in the application of IPC is a very important factor that contributes to patient safety and the quality of health services so that it will form a good hospital image. Barriers to professional cooperation can be a major cause of medical errors, treatment errors, or other unforeseen events. The purpose of this study was to analyze interprofessional collaboration in the care of patients with Diabetes Mellitus. The results of the case study show that the role of the health team in collaboration in nursing care has been implemented but has not been optimal. The implementation of IPC has not been optimally implemented because there are several obstacles such as the lack of communication between professions, none of the team members have participated in the application of IPC in health services, and stereotypes from one profession to another. So it is necessary to increase teamwork between health professionals, so that collaboration can be established optimally